An illustration to assist in comparing and remembering several multiplicity adjustment methods. (29th July 2016) - Hasler, Mario
Summary: There are many well‐known or new methods to adjust statistical tests for multiplicity. This article provides an illustration helping lecturers or consultants to remember the differences of three important multiplicity adjustment methods and to explain them to non‐statisticians.